(Effect of the Critical Sussecc Factors in the Sustainable Competitive advantage ) "Descriptive analytical studay in Al Mu’tasim General Contracting Company. - سعيد سناء عبد الرحيم; محمد تاغي زيدان (Journal of Economics and Administrative Sciences, 2014)
The objective of this research is to analyze the relationship between the Factors of critical success and sustainable competitive advantage, and I have tested Search Company Mu’tasim General Contracting, through applied on a sample of (90) manager, engineer and project manager, spread over sections and the company’s projects surveyed. has been selected sector construction industry as one of the sectors vital and important that play a major role in the advancement of Iraq’s infrastructure under the current circumstances, which epresent a set of Projects are Mu’tasim General Contracting construction implemented in the vernorate of Baghdad, a field of study in order to stand up to the reality of strategic management, management agents of the project, the factors associated with human resources, and their variants subsidiary as success factors critical impact on the success of the project management, and effect in sustainable competitive advantage of the company surveyed. Used the resolution as a key tool to collect data and information, for the purpose of access to the results he sought the researchers to test the two assumptions two major related relations link and influence between the variables of search key, and for data processing, use some means of statistical (such as the arithmetic mean, standard deviation, percentages, correlation coefficient ranks to Spearman coefficient simple regression ), have reached research findings most importantly, the existence of relations link correlation between the two variables and the presence of following moral elements of critical success in the sustainable competitive advantage, and based on search mechanism of the conclusions recommended that the company’s efforts surveyed to detect the elements of success critical time early through administrative practices and use them to achieve sustainable competitive advantage and objectives of the company surveyed.